2013
DOI: 10.1055/s-0033-1339681
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Hydrogen Peroxide by Diphenyl Diselenide for Highly Enantioselective Oxaziridinium Salt Mediated Catalytic Asymmetric Epoxidation

Abstract: The first reported use of benzeneperseleninic acid as a catalytic mediator for oxaziridinium ion catalysed epoxidation is described, providing reaction rates and ee values (up to 85%) similar to those reported when using oxone as the stoichiometric oxidant. A dual catalytic cycle is proposed, in which diphenyl diselenide is initially converted into the perseleninic acid, which in turn oxidises an iminium ion to the corresponding oxaziridinium species, thus facilitating asymmetric oxygen transfer to an alkene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
(10 reference statements)
0
14
0
Order By: Relevance
“…The authors used carbonates and hydrocarbonates as cocatalytic additives, capable of yielding percarbonates (HCO 4 – ) upon the interaction with H 2 O 2 ; the percarbonates converted the iminium cation into the oxaziridinium one, the latter being able to transfer the oxygen atom to the olefinic double bond. More recently, the authors reported the use of diphenyl diselenide for the same purpose: the latter afforded benzeneperseleninic acid, which in turn converted the iminium precatalysts of the type 71 into the active oxaziridinium salt . Good enantioselectivities (80–86% ee) were reported for the epoxidation of 1-phenylcyclohexene.…”
Section: Asymmetric Epoxidation Reactionsmentioning
confidence: 99%
“…The authors used carbonates and hydrocarbonates as cocatalytic additives, capable of yielding percarbonates (HCO 4 – ) upon the interaction with H 2 O 2 ; the percarbonates converted the iminium cation into the oxaziridinium one, the latter being able to transfer the oxygen atom to the olefinic double bond. More recently, the authors reported the use of diphenyl diselenide for the same purpose: the latter afforded benzeneperseleninic acid, which in turn converted the iminium precatalysts of the type 71 into the active oxaziridinium salt . Good enantioselectivities (80–86% ee) were reported for the epoxidation of 1-phenylcyclohexene.…”
Section: Asymmetric Epoxidation Reactionsmentioning
confidence: 99%
“…In this case, an inorganic additive must be employed, and the active intermediate can oxidize the organocatalyst, which in turn reacts with the olefin (Scheme ). Two recent examples of this mode of oxidation have been presented by Bulman Page, who uses HCO 3 −[63] and then Ph 2 Se 2 as the additive.…”
Section: H2o2: a Very Useful Oxidantmentioning
confidence: 99%
“…The ability of dioxiranes and oxaziridines to hydroxylate unactivated aliphatic C–H bonds intermolecularly in a site-selective manner had been previously established. N -Alkyl oxaziridinium salts, a separate but related class of oxidants, have been developed as reagents and catalytic intermediates for epoxidation and other oxidation reactions, including asymmetric transformations. However, the analogous C–H hydroxylation reactions employing oxaziridinium salts remain unexplored.…”
mentioning
confidence: 99%